Opportunities to reduce fatal injuries in Swedish agriculture using a prevention program - Lundqvist, Peter (Ubezpieczenia w Rolnictwie – Materiały i Studia, 2021)
Agriculture is one of the most dangerous sectors from a global point of view. This is also the situation in Sweden with many fatal and non-fatal injuries. The objective of this paper is an approach to make an overall evaluation of a national injury prevention intervention program (2009–2013). To reach the goal, the development of occupational fatalities in Swedish agriculture was examined during 15 years, 5 years before an intervention program, during the intervention program, and the five years after the intervention. Both official statistics, as well as unofficial statistics based on paper-clippings are used in this article. The overall results showed a decrease of the fatalities with about 45% during the 5 years of the intervention according to official statistics, but the effect was almost gone during the 5 years after. When adding the information from paper clippings a broader picture of agricultural fatalities is shown, including children, visitors, non-occupational incidents as well. In this article, suggestions are discussed as the importance of long-term interventions, possibilities of a digitalized OHS for farmers, international collaborations, and the value of the Vision Zero created by the International Section of the ISSA on Prevention in Agriculture.